2022
DOI: 10.3389/fnins.2022.997259
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency repetitive transcranial magnetic stimulation to the right dorsolateral prefrontal cortex engages thalamus, striatum, and the default mode network

Abstract: The positive treatment outcomes of low frequency (LF) repetitive transcranial magnetic stimulation (rTMS) when applied over the right dorsolateral prefrontal cortex (DLPFC) in treatment-refractory depression has been verified. However, the mechanism of action behind these results have not been well-explored. In this work we used simultaneous functional magnetic resonance imaging (fMRI) during TMS to explore the effect of LF rTMS on brain activity when applied to the right [RDLPFC1 (MNI: 50, 30, 36)] and left D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Similar effects are seen with rTMS. For example, right compared to left HF-rTMS is associated with greater dACC and dmPFC responses [69], and lf-rTMS can increase brain activity at the striatum, thalamus, and areas of the default mode network when applied to the right, but not to the left DLPFC [70]. Finally, TMSevoked responses collected during unpredictable threat, show that the right dlPFC seems to regulate activity in regions important to emotion This BOLD deactivation is attenuated by exogenous shock threat [71].…”
Section: Discussionmentioning
confidence: 97%
“…Similar effects are seen with rTMS. For example, right compared to left HF-rTMS is associated with greater dACC and dmPFC responses [69], and lf-rTMS can increase brain activity at the striatum, thalamus, and areas of the default mode network when applied to the right, but not to the left DLPFC [70]. Finally, TMSevoked responses collected during unpredictable threat, show that the right dlPFC seems to regulate activity in regions important to emotion This BOLD deactivation is attenuated by exogenous shock threat [71].…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with a role in CUD, left DLPFC function predicted cannabis versus money choice (Bedi et al, 2015). Combining positron emission tomography or fMRI with left DLPFC TMS has demonstrated that stimulating this region causes molecular and functional changes, respectively, in executive control and striatal brain regions (Strafella et al, 2001;Pogarell et al, 2007;Cho and Strafella, 2009;Hanlon et al, 2013;Gorelick et al, 2014;Caparelli et al, 2022). The ability of TMS to modulate glutamate and dopamine function in mesocorticolimbic circuits is consistent with its use as a tool to link brain activity with abuse-related behavior and as a potential treatment for drug use disorder, including CUD (Gorelick et al, 2014;Hanlon et al, 2018;Steele, 2020b;Kearney-Ramos and Haney, 2021).…”
Section: Intervention Protocolsmentioning
confidence: 89%
“…It does so with high accuracy. For example, in the case of bipolar disorder, TMS is purposefully positioned to affect the left dorsolateral prefrontal cortex [ 4 ]. This region plays a role in the regulation of emotional control.…”
Section: Discussionmentioning
confidence: 99%
“…These electromagnetic bursts act upon neurons with curved axonal processes at a right angle to the primary coil [ 3 ]. The electrical field induced in the neural tissue depolarizes the axons, eventually resulting in an action potential if the threshold is reached [ 4 ]. The ability to reach 120% motor evoked potentials (MEP) from 80% MEP is dependent on the type of coil and intensity of electrical current used [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation